Pengaruh Pembelajaran Dengan Strategi Ilustrasi Model Pizza Terhadap Hasil Belajar Matematika Ditinjau Dari Tingkat Kemampuan Penalaran Siswa Pada Materi Lingkaran(Penelitian Pada Siswa Kelas VIII SMP Negeri 1 Gondangrejo Tahun Ajaran 2014/2015) - Vitriawati, Utari, Prof. Dr. Budi Murtiyasa, M.Kom (2015)
The purpose of this research was to examine: (1) effect strategies illustration pizza models in terms of mathematics learning outcomes on circle learning, (2) effect mathematical reasoning ability in terms of learning outcomes on circle learning, (3) the interaction between strategy illustration pizza models and reasoning ability on circle learning. This type of research is based on a quasi-experimental design. The research population 189 of students was determined class VIII SMP Negeri 1 Gondangrejo. The research sample 64 students taken by two class it is VIIIA as experiments class and VIIIC as control class. The sampling technique using cluster random sampling. Questionnaire data collection techniques, test learning outcomes mathematics and documentation. The data analysis techniques used analysis variance two way with cells not same. The results of this research with significance using level of 5% was obtained that: (1) there is an effect in learning outcomes in terms of study strategy with used strategy illustration pizza models on circle learning. It based on multiple analysis variance two way that Fcount=4,65 > Ftable=4,01. (2) There is an effect in learning outcomes in terms of reasoning ability on circle learning. It based on multiple analysis variance two way that Fcount=17,27>Ftable=3,16. (3) There is no interaction between learning strategy illustration pizza models and reasoning ability for mathematics learning outcomes on circle learning. It is based on analysis variance two way that of Fcount=1,62<Ftable=3,16.